Novel therapeutic techniques for post stroke aphasia: a narrative review - Fazaila Ehsaan; Nazia Mumtaz; Ghulam Saqulain (Journal of the Pakistan Medical Association, 2022)
Aphasia, a language disorder, results from stroke involving cortical and subcortical structures. Aphasia lacks effective standardized treatment. Neuroimaging and behavioral research indicate that some interventions promote neuroplasticity. Research has suggested that noninvasive brain stimulation may be effective causing functional reorganization of language areas between both hemispheres. This reorganization evolves from different researches exploring novel procedures including transcranial magnetic stimulation and intracranial direct current stimulation, which may modulate cortical activity in aphasia. This paper reviewed these techniques while examining the casual role of specific regions of brain and the understanding of mechanism underlying for facilitator treatment effects of brain stimulation. For this literature was searched using search engines and databases like Medline, Web of Science and bibliography of published studies using “noninvasive brain stimulation, Post-stroke aphasia, Transcranial Magnetic Stimulation and Transcranial Direct Current Stimulation” as keywords. Of the 175 publications downloaded, 40 full text English publications were used for literature review.